An educational interventional study to compare conventional versus peyton’s method in training medical students on antenatal examination skills - Sethuraman, Dhivya; Revwathy, S.; Thangaraj, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Introduction of competency based medical education in India has made it imperative to teach and assess clinical skills in a uniform manner. Antenatal Examination is one of the core competency under Obstetrics and Gynaecology. We need to use effective instructional methods to teach skills. In this study, we have compared Peyton’s ‘four step approach’ with the conventional ‘see one, do one’ approach. Methods: A quasi- randomized crossover study with educational intervention was done among 49 medical students. They were divided into two groups (A and B). Students of group A were first trained on Antenatal examination using Conventional method and evaluated. With a gap of one week, they were re-trained on the same skill using Peyton’s method and re-evaluated again; the vice versa was for done in group B. Mann Whitney test was used to compare the difference in score between the two groups of students (A and B) and Wilcoxon Signed Ranks test was used to compare the student’s perception of both teaching methods. Results: The mean score obtained by students after the first training by Peyton’s (24.08±2.31) was greater than Conventional method (20.32±3.59) which was found to be statistically significant (Z=-3.54, p<0.5). Following the second training i.e crossover of the training technique, the marks obtained by both group of students were almost the same. Students perceived Peyton’s methods to be more interesting, interactive, better understanding and recall over conventional. Conclusions: Peyton’s method was found to be superior over conventional method of training medical students in Antenatal examination.